North Norway: An Invention? - Niemi, Einar (Journal of Northern Studies, 2007)
The article has as a starting point the fact that regions are one of the central political topics of today. Though regions have certain roots in history, they were not politicized until the nineteenth century, when they were “invented” as a tool for identity-shaping and development in the fringe areas of the state. The article operates with North Norway as a case in analyzing modern region-building processes and state regionalization strategies. This region is well suited as a case because of its particular position as a border area and its unique position in Norway’s political and economic history. The region-building process developed through distinct stages. In the 1970s North Norway came close to being understood as an identity region. Since the early 1990s, however, there have been fissures in this identity and the old regional visions have been under pressure from within as well as from without. In addition old tensions within the region have been disclosed. The most striking example is Finnmark, the northernmost county of the region, and of the nation as well, which through history has played a role in the margin. It is a kind of historical irony that the current development of the Norwegian “northern policy” programme together with the promising prospect of ocean-based oil and gas industry has put Finnmark in the forefront of future expectations.